A novel application for bolus remifentanil: blunting the hemodynamic response to Mayfield skull clamp placement. (February 2014) - Berger, M.; Philips-Bute, B.; Guercio, J.; Hopkins, T.J.; James, M.L.; Borel, C.O.; Warner, D.S.; McDonagh, D.L.
Abstract Objective: Neurosurgery often requires skull immobilization with a Mayfield clamp, which often causes brief intense nociceptive stimulation, hypertension and tachycardia. Blunting this response may help prevent increased intracranial pressure, cerebral aneurysm or vascular malformation rupture, and/or myocardial stress. While various interventions have been described to blunt this response, no reports have compared administration of a propofol versus a remifentanil bolus. Methods: We retrospectively analyzed the hemodynamic response to Mayfield placement in over 800 patients who received a prior propofol or remifentanil bolus from 2004 to 2010. Results: Patients who received remifentanil experienced a 55% smaller increase in heart rate (p < 0.0001) and a 40% smaller increase in systolic blood pressure (p < 0.0001) after Mayfield placement than patients who received propofol. These data were retrospectively obtained from patients who were not randomized to receive remifentanil versus propofol, and hence these data could be subject to possible confounding. Nonetheless, these differences remained significant after multivariate analysis for possible confounding variables. Conclusions: Thus, a remifentanil bolus is more effective than a propofol bolus in blunting hemodynamic responses to Mayfield placement, and possibly for other short, intense nociceptive stimuli.